Residents` Satisfaction Evaluation of Housing and Environment Quality of Rumah Deret Tamansari, Bandung - Sekartaji, Dian; Abadi, Agustinus Adib; Siregar, Mohammad Jehansyah; Yuwono, Tri; Liandrawani, Novi; Imaduddin, Rashif; Isnandya, Adhitya Rizky; Mawarsari, Daffa (Jurnal Arsitektur, 2026)
The slum relocation program is a government strategy to provide decent, safe, and affordable housing for low-income communities. The Rumah Deret Tamansari (RDTS) in Bandung City is a relocation project for residents of the Tamansari slum area that aims to improve the quality of housing and the urban environment. This study aims to evaluate the level of satisfaction of residents with the quality of housing and the environment of RDTS. The research method uses a mixed approach through the distribution of questionnaires to 24 residents, semi-structured interviews, and field surveys to assess the physical condition of the building and environmental facilities. Aspects evaluated include room size, thermal comfort, lighting, cleanliness, security, accessibility, public facilities, and social adaptation of residents. The results indicate that 63% of respondents expressed overall satisfaction with the housing and environmental quality of RDTS. Satisfaction levels were highest for location and accessibility (over 80% agreement), cleanliness (71%), and security (75%). In contrast, dissatisfaction was most evident in domestic space size (42% dissatisfied) and shared facilities management, particularly elevator functionality (55% dissatisfied). The field survey revealed that the building quality is relatively good with the implementation of passive designs such as inner courts and cross-ventilation. This study emphasizes the importance of continuous evaluation and participatory management to realize sustainable vertical housing that is oriented towards the housing quality of residents’ life.